On the Scope of Egalitarian Justice - Heath, Joseph (Les ateliers de l'éthique / The Ethics Forum, 2006)
It is not clear whether the social contract is supposed to merely supplement the unequal gains that individuals are able to make through the exercise of their natural endowments with a set of equal gains secured through social cooperation, or whether the social contract must also compensate individuals for the effects of these natural inequalities, so that they literally become all equal. The issue concerns, in effect, whether natural inequality falls within the scope of egalitarian justice. I think it is fair to say that the majority of egalitarians assume that the principle of equality imposes an obligation to redress natural inequality. Yet there is no consensus on this issue. David Gauthier has made the rejection of the principle of redress a central component of his project. It has often escaped notice that John Rawls also rejects the principle of redress. Thus it is not just anti-egalitarians who reject the principle of redress. There is a current of egalitarian thought – which we might call, for lack of a better term, narrow-scope egalitarianism – which also rejects this principle. In this paper, I would like to show that there is considerable wisdom in the narrow-scope egalitarian position. Many of the problems that lead theorists to reject egalitarianism in its entirety are a consequence, not of the principle of equality per se, but rather of the commitment to redress natural inequality. The narrow-scope view avoids all of these difficulties.